Utfodringsalternativ till vitryggig hackspett (Dendrocopos leucotos) på djurpark - Hiertonn Oscarsson, Maria (SLU/Dept. of Animal Environment and Health (until 231231), 2016)
In the last decades, the Swedish forests has changed drastically in a relatively short time. One of the species most affected by the change is the white-backed woodpecker (Dendrocopos leucotos) and is therefore endangered in Sweden. The woodpecker is almost exclusively an insectivore and gets their main feed by hacking it out of older hardwood trees. To restore a population, the zoo Nordens Ark keeps woodpeckers with the aim of replacing new individuals in Sweden. In the current situation woodpeckers at Nordens Ark are feed through a food bowl. The aim of the study was to evaluate a new feeding option that would include the woodpecker having to hack to access their food. It was hoped that a new feeding option would reduce feed wastage, and act as a natural way of feeding woodpeckers. The study was conducted at Nordens Ark during seven days with eight woodpeckers held in pairs. The feeding option that would be tested consisted of a log of wood with four cavities therein mealworms would be placed and then plugged with the help of wooden pegs. Two logs were placed in each cage on existing tree trunks and was replaced once a day. Eeach log where examined to rate how much the woodpeckers had hacked and if they managed to get hold of the mealworms. Each cage was observed for 2x10 minutes/day to see the woodpeckers behaviour towards the logs. Two randomly selected cages had free access to feed from a bowl during the study, while the remaining two cages had limited access. The aim was to see if the motivation to hack changed with the availability of food. According to the theory contrafreeloading, free access to food does not mean that an animal chooses the easy way to get their food, but rather choose to work to achieve it. This phenomenon is believed by many researchers is about information gathering. It serves the animal in exploring different options when natural conditions can cause that food resources moves from one day to another. The results showed that six of the eight individuals who participated in the study has at least ones during the studie hacked on the logs. The cages that had free access to feed has showed highest indication on the hackrating and have got hold of the feed from the stocks in the highest degree. Two cages has hacked relatively high in relation to the other two. Three of the four cages succeeded at least ones to cater to the feed. When it was a small study, it can not be determine completely whether the logs may seem like a good feeding option or if contrafreeloading is what motivated woodpeckers hacking. For some individuals, the logs, however, seem like a good enrichment. As an enrichment instead of a feeding option, the log would not reduce feed waste but to contribute to the woodpecker's welfare. Further study is necessary to draw larger conclusions. This study might be useful as a pilot study for future projects.